Penerapan Model Pembelajaran Kooperatif Model Make A Match Untuk Meningkatkan Keterampilan Membaca Intensif Dalam Memahami Teks Bacaan Pada Mata Pelajaran Bahasa Indonesia di Kelas III SD GMIM II Tomohon - Rindengan, Mersty E. (Jurnal Ilmiah Wahana Pendidikan, 2024)
Problems in student education always arise along with the development of students' abilities in following lessons. For this reason, in facing all changes and demands of society in general and environmental needs. In accordance with the reality found at the GMIM II Tomohon Elementary School, it shows that many students have difficulty reading intensively in understanding reading texts, and many elementary school teachers state that they have difficulty teaching intensive reading. The application of learning using the Make A Match Model is a step in solving Indonesian language problems in intensive reading and understanding reading texts, where by using this model students can more easily understand intensive reading in understanding reading texts and remember the lessons they have been taught. This is because students are exposed directly to real things that can be seen and felt so that they can make an impression on students that cannot be forgotten. The aim of this research is to improve intensive reading skills in reading Indonesian texts in class III of SD GMIM II Tomohon in implementing the Make A Mach learning model. The research results obtained in this study through the application of the Make A Match learning model are that: (1) it is proven to improve student learning outcomes, (2) Make A Match is cooperative learning that can foster student cooperation in answering questions by matching existing cards. in their hands, (3) The learning process is more interesting and it appears that most students are more enthusiastic about participating in the learning process, and (4) Student activity is very visible when students look for their respective pairs of cards.